VD_FINDINFO AI 33/15 - 35/2016 vom 11. Februar 2016 - VD Tribunal cantonal (2016)
RENTE D'INVALIDITÉ, DROIT À LA PRESTATION D'ASSURANCE, DÉBUT, DEGRÉ DE L'INVALIDITÉ | 28 al. 1 LAI, 29 al. 1 LAI, 29 LPGA